Novel Acute Retinal Artery Ischemia and Reperfusion Model in Nonhuman Primates. Issue 8 (August 2020) - Gao, Yuan; Wu, Di; Liu, Dachuan; Huber, Mitchell; Chen, Jian; Wang, Xizhe; Lv, Kui; He, Xiaodu; Yang, Huiqing; Ren, Changhong; Ding, Yuchuan; Ji, Xunming; et al.
Abstract : Background and Purpose: The retina, as an externally located neural tissue, offers unique advantages in investigating the effect of therapeutic intervention on the brain. In this study, we put forth a clinically relevant model of retinal ischemia and reperfusion in nonhuman primates. Methods: Acute retinal artery ischemia and reperfusion was induced by injecting an autologous clot into the ophthalmic artery of adult rhesus monkeys, and recanalization was achieved by focal thrombolysis with tPA (tissue-type plasminogen activator). Digital subtraction angiography and fluorescein angiography were used to evaluate blood flow in the retina and the choroid. Electroretinogram, optical coherence tomography, and hematoxylin and eosin staining were used to evaluate the structure and function of the retina after ischemia. Results: Digital subtraction angiography and fluorescein angiography images confirmed occlusion of the ophthalmic and central retinal arteries, as well as recanalization after tPA thrombolysis. Electroretinogram indicated retinal functional damage following ischemia, and thrombolysis partially rescued its impairment. Optical coherence tomography and hematoxylin and eosin staining revealed ischemia-induced changes in the retina, and tPA partially mitigated these damages. Conclusions: This novel acute retinal artery ischemia and reperfusion model in rhesus monkeys may closely simulate retinal ischemia/reperfusion in clinical practice and provide an optimal platform for screening neuroprotective strategies. Abstract : Supplemental Digital Content is available in the text.